Perbankan Islam di Indonesia: Implikasinya dengan Politik, Hukum, dan Islam - naziarto sr (Fakultas Hukum Universitas Islam Indonesia, 2002)
The appearance of Islamic Banking in Indonesia has closely correlation to the real politics and the authority ofgovernment (new order) under fower center' Soeharto as a President the former at that time. Because there is magnet mutually tug of role and the impact of major Moslem in politics to defend his authority. The reality ofcoming for Islamic banking on June in 1992 is as accommodaf/on for economic and political dimension in New Order state by the power ofIslam. The insitutution ofbanking acts which is valid today have not met and given the whole opportunity for dynamicfzation ofIslamic bankingin Indonesia. Itis natural that to be happen because viewed from historical fact that the process ofreconstructing for banking acts was done in abnormal era.